AIR MATH

Math Question

The altitude of a right triangle divides the triangle into two triangles similar to each other and to the original triangle. So, in the diagram below, \( \triangle E F G \sim \triangle F H G \sim \triangle E H F \).
Complete the proof that \( E F^{2}+F G^{2}=E G^{2} \).
Since \( \triangle E F G \sim \triangle E H F \), then \( \frac{E F}{E G}=\quad \quad \). You can rewrite this equation as
-. Similarly, since \( \triangle E F G \sim \triangle F H G \), then \( \frac{E G}{F G}= \) -. You can rewrite
this equation as
Now, using the
- \( E F^{2}+F G^{2}=E F^{2}+E G \cdot H G \). Then, by
substitution, \( E F^{2}+F G^{2}= \)
-. So, \( E F^{2}+F G^{2}=E G \cdot(E H+H G) \) by the
- Because \( E H+H G= \)
by the Additive
Property of Length, \( E F^{2}+F G^{2}=E G \cdot E G \) using substitution. Therefore, \( E F^{2}+F G^{2}=E G^{2} \).

Solution

solution

AIR MATH homework app,
absolutely FOR FREE!

  • AI solution in just 3 seconds!
  • Free live tutor Q&As, 24/7
  • Word problems are also welcome!
appstoreplaystore

Scan the QR code below
to download AIR MATH!

qrcode